Well Furnished: A Study on The Online Furniture Rental Start-Ups in India - Alukal, Paul Pratap; Mathew, Nikhil Jose (SFIMAR Research Review, 2022)
Today, people are inclined towards accepting what is convenient, hassle-free and are open to experiencing different products available online. Since owning furniture requires a good investment, it may not be feasible to keep trying different furniture designs every now and then. While relocating, people need furniture for their house. Buying new furniture may be an expensive option. Taking this into consideration, start-ups have come up with the appropriate offering- rental furniture. Customers now have access to a variety of furniture designs by just paying the subscription fee. This helps them to upgrade the look of their homes as per their changing tastes. This study has tried to understand the business models of the online rental furniture start-ups in India. It has also tried to get a glimpse of the general awareness and perception among the public regarding the offerings of these start-ups. A survey was conducted of 158 respondents. From the survey some of the findings were that majority of the respondents were aware about the concept of renting furniture online, many believed that renting furniture addressed the temporary requirements of the user and it made sense to rent furniture while staying in a rented house or apartment.